A longitudinal study depicting persistence of COVID-19 antibodies after half a year using chemiluminescent microparticle immunoassay among healthcare workers and frontline workers in Mumbai, India’s largest metropoli - Rujuta S. Hadaye; Sachee Agrawal; Mangala Gomare; Daksha Shah; Abhiram Kasbe; Jayanthi Shastri; Gulnar Khan; Pradnya Chandanshive; Nirjhar Chatterjee; VL Anand Vijay (Journal of Family Medicine and Primary Care)
Introduction: Antibodies play a role in herd immunity, and studies estimate that COVID-19 antibody protection lasts approximately 1 to 4 months following COVID-19 vaccination and 6 to 8 months following infection. As healthcare workers and frontline workers were highly exposed to the infection, it is necessary to know if they have developed immunity against COVID-19. Aim: To estimate the seroprevalence of SARS-CoV-2 antibodies among health care workers and frontline workers in Mumbai qualitatively and quantitatively and observe the change in antibody levels after 6 months. Material and Methods: This longitudinal study was conducted over 9 months in two phases among 1544 healthcare workers (HCWs) and 1555 frontline workers (FLWs) aged above 18 years in Mumbai, Maharashtra, India. Participants’ blood samples were analyzed using the SARS-CoV-2 IgG-II Quant assay for the qualitative and quantitative determination of IgG antibodies to SARS-CoV-2. A follow-up was done after 6 months. Results: A total of 2733 (88.2%) of the 3099 participants were followed up in Phase II, which included 1370 (50.1%) FLWs and 1363 (49.9%) HCWs. The study found a seropositivity rate of 99.9% with a significantly higher antibody titre in BEST (public transport) workers, those vaccinated with precautionary doses, those vaccinated with precautionary doses with a history of confirmed COVID-19 disease, and participants over 45 years. Conclusions: The study findings indicate a widespread seroconversion against COVID-19 and a beneficial effect of precautionary dose in addition to two doses of the COVID-19 vaccine. The role of subclinical infection needs to be explored.